Plasma miRNAs in polycystic ovary syndrome drive endometrial cancer progression: insights into molecular pathways and therapeutic targets - Xuedan Lai; Ling Wu; Peihong Lin; Lijiao You; Jianwen Ye (Discover Oncology)
Abstract Polycystic ovary syndrome (PCOS) is a known risk factor for uterine endometrial cancer (UCEC), but its underlying mechanisms remain unclear. MicroRNAs (miRNAs) could provide insights into these mechanisms and reveal potential therapeutic targets. Differential miRNA expression was analyzed in plasma exosomes from 15 PCOS and 15 control samples. Survival analysis assessed the prognostic value of these miRNAs in UCEC. MiRNA-target gene interaction networks and gene co-expression analyses were used to explore molecular mechanisms. Validation was performed using experimental data from Ishikawa cells treated with six candidate drugs. Among the 15 differentially expressed miRNAs, 12 were up-regulated and 3 were down-regulated in PCOS. Twelve of these miRNAs were associated with UCEC overall survival, with miR-142, miR-424, and miR-331 acting as protective factors, while the remaining 9 miRNAs were identified as risk factors. MiRNA-target network highlighted key genes such as PHF8, LCOR, SFT2D3, E2F1, and ESR1, which were found to be prognostic for patient survival. Further gene expression and co-expression analyses based on miR-424 and miR-330 expression revealed significant alterations in gene expression and cellular processes related to UCEC. Two-sample Mendelian randomization analysis identified potential causal relationships between AURKA gene expression and PCOS or UCEC. Testosterone and estradiol might have adverse roles in UCEC, while drugs like troglitazone, valproic acid, retinoic acid, and progesterone demonstrated various effects on gene expression and cellular processes. Our findings suggest that aberrant miRNA expression, particularly miR-330 and miR-424, may play crucial roles in UCEC progression. The identified miRNAs and candidate drugs may serve as potential therapeutic targets for UCEC, but further research is required to validate and explore their clinical applications.